Integration of CNTs thin film for sensing and actuating micro structures - Van, Dau Thanh; Tung, Bui Thanh; Dzung, Dao Viet; Sugiyama, Susumu (Vietnam Journal of Mechanics, 2012)
This paper reports the top-down fabrication of CNTs thin film on MEMS structure to develop sensing and actuating micro structures. In particular, this paper review the integration of CNTs film in application of silicon micromirror based on angular vertical comb actuator, development of microstructures with piezoresistive effect and Seebeck effect.